The director and his relationship with the quality, innovation and learning committee - Gonzales-Santos, Zoraida (2021)
The management of the director of an educational institution is essential for the achievement of student learning; In this sense, the Ministry of Education implements tools for principals to manage the development of the learning levels of Regular Basic Education students. For this reason, he formulated a guide to form the Quality, Innovation and Learning Commission, which the director must execute. The objective of this research was to know the status of executive leadership and the appointment of the Quality, Innovation and Learning Committee in the I.E. Filother Mendoza Campos de Cauri, Lauricocha. The type of research was qualitative, descriptive level and the interpretive method, with a probabilistic sample made up of the directive and teaching staff. The results regarding managerial leadership in Domain 1 indicate: Regular 60%, Excellent 37% and Poor 3%; In Domain 2, they indicate: Regular 50%, Excellent 40% and Poor 10%. Regarding the conformation of the Quality, Innovation and Learning Commission, regarding the Appointment of the commission, they indicate: Deficient 47%, Regular 40%, Excellent 13%; Regarding the operation of the commission, they indicate: Regular 57%, Excellent 37% and Deficient 7%. It was concluded that: a) The status of executive Leadership is Regular, both in Domain 1 and in Domain 2; b) The status of the Appointment of the Quality, Innovation and Learning Commission is Deficient with respect to the Appointment of the commission; and, Regular in the functions of the quality commission.